REPRESENTASI NILAI INQUIRY DAN OPEN MINDED DALAM PELAJARAN UNIT OF INQUIRY (UOI) SISWA KELAS 2 DAN 3 SD BERBASIS IB CURRICULUM - Vicensia Araya; Leonardha Pascha Dewi; Maria Agustina Amelia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the representation of the values of inquiry and openmindedness in the Unit of Inquiry (UOI) learning among grade 2 and grade 3 students in an elementary school implementing the International Baccalaureate (IB) curriculum. The research employed a qualitative descriptive method with data collected through observation, interviews with classroom teachers, and documentation of students’ UOI products. The findings show that UOI learning provides meaningful opportunities for students to develop curiosity, conduct investigations, and build conceptual understanding through inquiry activities. The value of inquiry was manifested in students’ ability to ask questions, explore ideas, and reflect on their findings, while the value of open-mindedness appeared in their willingness to listen to others, accept diverse perspectives, and cooperate in group discussions. The representation of both values developed gradually in accordance with the students’ cognitive levels—grade 2 students showed more concrete inquiry behavior, whereas grade 3 students demonstrated more abstract and reflective thinking. UOI learning also encouraged students to integrate knowledge across disciplines and apply it in real-life contexts, proving that the IB curriculum effectively supports character and critical thinking development through transdisciplinary inquiry.